The impact of age on anxiety in Covid-19 patients in quarantine wardwards. Issue 2 (7th February 2022) - Sun, Peng; Fan, Duo-Jiao; Li, Heng-Zhou; He, Tao; Zhang, Xiao-Kun; Wang, Guang; Chen, Wan-Li; Liu, Li-Min
ABSTRACT: This study aimed to explore which age group out of the patients in quarantine wards with novel coronavirus pneumonia is the most susceptible to anxiety. The data of 32 Covid-19 patients isolated in the quarantine wards of the second Infectious Diseases Department of Baoding Hospital and 71 Covid-19 patients in Tangshan City Infectious Disease Hospital from January 24 th to March 5 th, 2020, a total of 103 patients, were analyzed. Among these patients, 97 isolated patients were scored with a self-rating anxiety scale (SAS) score seven days after quarantine, and the correlation between age and score was analyzed. These 97 isolated patients were then divided into three groups according to age: group A (up to 35 years old), group B (36–60 years), and group C (over 60 years). One-way analysis of variance was used to compare the scores among groups. The Q-test was used for pairwise comparison.P < 0.05 was considered statistically significant.There was a negative correlation between age and SAS score in isolated Covid-19 patients, and the differences in the score among groups were statistically significant. Patients under 35 years old were more prone to anxiety when they were isolated for seven days. Isolated patients aged up to 35 years old need more attention from quarantine medical staff, communication should be strengthened, and psychological intervention from psychotherapists should be given if necessary.